Merumuskan Pemikiran Ekonomi Muslim Tentang Rasionalitas dalam Perilaku Konsumen - Lia Istifhama (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Rationality is the characteristic of any action, belief, or desire,that makes their choice optimal under a set of constraints. It is a normativeconcept of reasoning in the sense that rational people should deriveconclusions in a consistent way given the information at disposal. It refers tothe conformity of one's beliefs with one's reasons to believe, or with one'sactions with one's reasons for action. However, the term